2018
DOI: 10.1002/dvg.23220
|View full text |Cite|
|
Sign up to set email alerts
|

Rapamycin rescues BMP mediated midline craniosynostosis phenotype through reduction of mTOR signaling in a mouse model

Abstract: Craniosynostosis is defined as congenital premature fusion of one or more cranial sutures. While the genetic basis for about 30% of cases is known, the causative genes for the diverse presentations of the remainder of cases are unknown. The recently discovered cranial suture stem cell population affords an opportunity to identify early signaling pathways that contribute to craniosynostosis. We previously demonstrated that enhanced BMP signaling in neural crest cells (caA3 mutants) leads to premature cranial su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 75 publications
1
13
0
Order By: Relevance
“…A study published recently implied that, when enhancing the expression of BMP signaling in neural crest cells, loss of suture mesenchymal stem cells have been observed. Moreover, higher degree of cell death has also been illustrated in mutant mice 43. Although studies published till now are far from making a conclusion, a speculation could be provided here is that depletion of mesenchymal stem cells within cranial sutures resulted from cell death /apoptosis might be a cellular mechanism of suture premature fusion.…”
Section: Genetic Parameters In Skull Vault Developmental Biologymentioning
confidence: 76%
See 2 more Smart Citations
“…A study published recently implied that, when enhancing the expression of BMP signaling in neural crest cells, loss of suture mesenchymal stem cells have been observed. Moreover, higher degree of cell death has also been illustrated in mutant mice 43. Although studies published till now are far from making a conclusion, a speculation could be provided here is that depletion of mesenchymal stem cells within cranial sutures resulted from cell death /apoptosis might be a cellular mechanism of suture premature fusion.…”
Section: Genetic Parameters In Skull Vault Developmental Biologymentioning
confidence: 76%
“…Studies have been processed for years to investigate the correlations between craniosynostosis and dysregulation of cellular proliferation and differentiation, while the role of apoptosis of cells during cranial development have been proposed by some authors 39-43. Studies indicated that apoptosis is involved in the development of both nasal cartilage and calvarial bones 44, 45.…”
Section: Genetic Parameters In Skull Vault Developmental Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…59,60 Furthermore, mTOR signalling was shown to play a critical role in craniofacial development since mTOR disruption in mesoderm-derived mesenchymal cells was found to inhibit long bone development and cause calvarial defects. 58 Of interest, PC1 has been shown to regulate the mTOR signalling pathway in ADPKD studies 37,38,55,57 with mTORC1 further downregulating the expression of PC1 via a feedback loop. 56 A previous study from our research team has demonstrated a connection between polycystins and mTOR signalling in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…mTORC1 and mTORC2 are considered as critical regulators of early embryonic development, since disruption of their key components, Raptor or Rictor results in early embryonic death prior to craniofacial organogenesis 59,60 . Furthermore, mTOR signalling was shown to play a critical role in craniofacial development since mTOR disruption in mesoderm‐derived mesenchymal cells was found to inhibit long bone development and cause calvarial defects 58 …”
Section: Discussionmentioning
confidence: 99%